Evaluation of Governance and Measurement of Maturity Levels System Plastic Injection Company Information Using COBIT 2019 and Luftman Maturity Model - Nurtjahjo, Ferdinandus Andrew; Harnadi, Bernardinus; Koeswoyo, G.Freddy (Soegijapranata Catholic University, 2024)
Organization for managing information technology often doesn't work effective so that result the company's workflow becomes irregular . This research initiates governance system PT Amaryllis information Charisma Brilliant by using measurements level IT maturity based on the Luftman Maturity Model and COBIT 2019 framework in the Align, Plan, and Organize (APO) domain. measure by method Luftman maturity model done by share questionnaire related criteria communication , competence , governance , partnership , space scope architecture , and expertise in space scope IT maturity in the company . Evaluation of IT governance using the COBIT method is carried out by opening the APO domain in levels management company to assess weakness system information and can provide recommendation related to improvement performance company . Measurement evaluation results level IT maturity shows company on criteria communication , partnerships , and expertise are included in level 4 ( Improved Process ), meanwhile criteria competence , governance and partnerships enter level 3 ( Established Process ) so this research is recommended company to make structural changes organization under the director directly in implementing service level and focus agreements to business integration using third parties in making IT strategies. Whereas IT governance evaluation results using COBIT 2019 APO domain that companies in sub domains APO02, APO03, APO04, APO07, APO09, APO13 enter level 4 ( Predictable Process ), while sub domains APO01, APO05, APO06, APO08, APO10, APO11, APO12, and APO14 enter level 5 ( Optimizing Process ). Acquired weaknesses that is Not yet fulfillment committee executive IT related and not done testing IT- based by all employees so this research recommends company to form committee special executive in management related to IT and management testing IT- based by a special team formed by the company.